2011
DOI: 10.1515/rns.2011.037
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to improve neurodevelopmental abnormalities in Down syndrome?

Abstract: Down syndrome (DS) is a genetic pathology caused by the triplication of human chromosome 21. Although individuals with DS have various medical problems, intellectual disability is the most invalidating aspect of the pathology. Despite numerous efforts, the mechanisms whereby gene triplication leads to the DS phenotype have not been elucidated and there are, at present, no therapies to rescue brain developmental alterations and mental disability in individuals with DS. In this review, we focused on the major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 324 publications
(500 reference statements)
4
68
0
2
Order By: Relevance
“…As mentioned above, evidence for the role of DYRK1A in various DS phenotypes is partially derived from studies performed in several segmental trisomic mouse models of DS that overexpress different sets of orthologous genes of human chromosome 21 (Hsa21), including Dyrk1A (Rueda et al, 2012;Bartesaghi et al, 2011) and in transgenic mice overexpressing DYRK1A in artificial bacterial or yeast chromosomes or carrying extra copies of the corresponding murine cDNA (De la Torre et al, 2014;Ahn et al, 2006;Altafaj et al, 2001;Smith et al, 1997).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, evidence for the role of DYRK1A in various DS phenotypes is partially derived from studies performed in several segmental trisomic mouse models of DS that overexpress different sets of orthologous genes of human chromosome 21 (Hsa21), including Dyrk1A (Rueda et al, 2012;Bartesaghi et al, 2011) and in transgenic mice overexpressing DYRK1A in artificial bacterial or yeast chromosomes or carrying extra copies of the corresponding murine cDNA (De la Torre et al, 2014;Ahn et al, 2006;Altafaj et al, 2001;Smith et al, 1997).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TS mice replicate many DS-like abnormalities, including alterations in behavior, learning and memory, brain morphology and hypocellularity, neurogenesis, neuronal connectivity and electrophysiological and neurochemical processes (Rueda et al, 2012;Bartesaghi et al, 2011). Similar to DS individuals, the TS mouse also shows age-dependent cognitive decline and degeneration starting at the age of 6 months, including cholinergic and noradrenergic neuron degeneration, increases in the levels of APP protein and Aβ peptides and tau hyperphosphorylation (Millan Sanchez et al, 2012;Rueda et al, 2010;Netzer et al, 2010;Liu et al, 2008;Seo et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This defect translates into a diffused reduction in the number of neurons across the whole DS brain. 3,6 The increase in the repertoire of functions along the time course of mammalian evolution is due to an increase in the relative number of neurons populating the brain, culminating in the unique brain functions possessed by nonhuman and human primates. Therefore, the reduced neuron number in DS is very likely a key determinant underlying the poor performance of individuals with DS in many cognitive functions and behaviors.…”
Section: The Gene Burden Impairs Brain Development In Down Syndromementioning
confidence: 99%
“…Brain abnormalities in DS were thought to be irreversible, but during the last decade several preclinical studies have shown that in mouse models of DS it is possible to improve or even rescue the major neurodevelopmental alterations of the trisomic brain. [3][4][5] These discoveries obviously give new hope for therapeutic interventions in individuals with DS.…”
Section: Introductionmentioning
confidence: 99%
“…Estas alteraciones del neurodesarrollo limitan en grado variable el desempeño cognitivo y las funciones neuropsicológicas (Bartesaghi, Guidi & Ciani, 2011). En este sentido, la afectación hipocampal compromete la memoria explícita.…”
Section: Síndrome De Downunclassified